Regulating Pre-implantation Genetic Diagnosis. - A. M. McLean, Sheila (Biomedical law and ethics library., 2012)
The successful achievement of pregnancies following pre-implantation genetic diagnosis (PGD) was first reported in April 1990. The technology is often used for patients who are at substantial risk of conceiving a pregnancy affected by a known genetic disorder, however from this technology other more controversial uses have arisen such as HLA typing to save the life of a sibling, gender selection for social reasons, the prevention of late onset diseases, or the prevention of diseases which may be genetically predisposed to developing such as breast cancer. The technology surrounding PGD is cons.